Dynamics of Power in Poetry of the Era of Fooling in the Era of Globalization Statistical Studies - Naila Synta Ramadani; Rosmawaty Harahap (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2024)
The dynamics of power in poetry during the era of modernization in the era of globalization, statistical studies are analyzing that focus on how power is expressed through poetry in the context of the era of globalization. The background to this problem involves how poetry as an art form can be used to express power in various forms, including social power, cultural power, and political power. The method used in this research is descriptive qualitative, which is a research method for collecting data in the form of descriptive narratives both verbally and in writing. The results of this research show that power in poetry in the era of modernization in the era of globalization of stylistic studies can be seen in various ways. Social power can be expressed through poetry that expresses the experiences and views of people from various social and cultural backgrounds. The power of culture can be seen in poetry which describes how culture and traditions are applied in everyday life. Political power can be expressed through poetry that expresses different political views and aspirations. The aim of this research is to understand how power is expressed through poetry in the era of globalization and how poetry can be used to express power in various forms. Thus, it is hoped that this research can contribute to a deeper understanding of how poetry can be used as a means of communication and expression in an increasingly complex and dynamic era of globalization.